Heterosis and heterobeltiosis for morpho-physical, phenolics, flavonoids and antioxidants in grape (Vitis vinifera) hybrids - SAHOO, TANUSHREE; VERMA, M K; SINGH, S K; THAKRE, MADHUBALA; SHARMA, R R; JAISWAL, SARIKA (The Indian Journal of Agricultural Sciences, 2017)
Eleven coloured hybrids and their 9 parental genotypes were evaluated for bunch weight, berry weight, juice recovery, total soluble solids (TSS), total monomeric anthocyanins (TMA), total phenolics (TP), total flavonoids (TF) and antioxidant activities (AOX) in terms of CUPRAC, FRAP and DPPH. Data analysis indicated significant differences in the traits under study. The substantial positive mid-parent and better-parent heterosis was found for TSS, TMA, total flavonoids, CUPRAC and FRAP. The negative mid-parent heterosis and heterobeltiosis was exhibited for bunch weight, berry weight, juice recovery, total phenolics, and DPPH activity. The results suggest that hybrid ERR2P36 and hybrid 16/2A-R1P8 can be considered as good source of natural antioxidants and having higher TSS content.